Neoliberal abandonment in disability housing provision: a look at England and Chile. Issue 5 (28th May 2019) - Power, Andrew; Gaete-Reyes, Mariela
Abstract: Public or 'social' housing provision in many nations in the Global North is increasingly being driven by neoliberal strategies that include austerity cuts and market-led privatization. This context raises an important question of how likely the state's reliance on the private sector can ensure that housing remains available and accessible to more disadvantaged low-income groups. To help answer this question, we draw on a comparative study of social housing provision for disabled people in England and Chile; two pioneers of neoliberal reform in this sector. Using interviews with key stakeholders, our findings reveal that the neoliberal reform strategies being employed have tended to dilute the statutory duties of providing accessible housing and to undermine disabled people's choices in finding appropriate homes. Such lessons are timely and important in order to remain cognisant of the spaces of neoliberal abandonment that are leaving many people unable to gain access to appropriate housing.